Some Comparative Aspects of Educology Studies in Lithuania and Nordic Countries - Tinfavičienė, Ingrida (Acta Paedagogica Vilnensia, 2001)
Educational studies have a long history at the universities of Nordic countries. History of educational studies in Lithuania has not such a long history and is still m1der developing process. That's why it's useful and interesting to take o look and see bow educational studies have been developed and what kind of content were chosen. The brief look at the content of study programs let us compare them with educational studies in Lithuanian. One of difference, which could be found, is that in all Nordic countries studies of education starts at BA level. In Lithuanian only very few educational studies programs (for example, social education) are possible to study as BA studies. One more difference is that specialization at Nordic countries universities is much narrower comparing with specialization in Lithuanian universities. It means, that fewer subjects are studied and much more hours are dedicated for it. It helps students get mare deep knowledge of certain narrow area in pedagogical field and obtain certain skills, which are required for work in that field. At the other hand, the same knowledge and skills are obtained at Lithuanian universities also, but students have less time for it , so it could be an explanation why such a wide range of courses are offered on compulsory and optional level.
Keywords: Higher education; university; educational studies; studies programs.